2019
DOI: 10.1108/et-02-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

A review of entrepreneurship education research in the special issues of Education + Training journal

Abstract: Purpose The purpose of this paper is to discuss the course of entrepreneurship education (EE) research within the framework of entrepreneurship. The study is based on the results of previous research published in the annual double special issues of Education + Training (E+T) journal. In this context, it examines the role of EE at different levels of education; EE interactions and approaches; the effects of the variety of variables on EE; and the grouping of these variables into clusters. Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…The TPB of Ajzen (1991) has been frequently applied to entrepreneurship in the field of education research (Aamir et al , 2019), and a recent meta-analysis confirms that it can predict EI and behavior (Schlaegel and Koenig, 2014). This theory states that three variables influence intentions (Ajzen, 1991): ATB, PBC, and SN.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The TPB of Ajzen (1991) has been frequently applied to entrepreneurship in the field of education research (Aamir et al , 2019), and a recent meta-analysis confirms that it can predict EI and behavior (Schlaegel and Koenig, 2014). This theory states that three variables influence intentions (Ajzen, 1991): ATB, PBC, and SN.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In our work, HF is analysed as a cause of EI, not a consequence as it has traditionally been investigated (VanderWeele et al, 2020), providing a broader understanding of the topic. Secondly, although a substantial number of studies have been conducted on entrepreneurship education, the literature on this topic still lacks content at the primary and upper secondary levels (Aamir et al, 2019). Our findings suggest that HF increases perceived EI and that ESE partially mediates this relationship.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, entrepreneurship education in upper secondary education can influence entrepreneurship and increase EI rates in students (Garrido-Yserte et al, 2020). Research has shown a positive reaction from students at the upper secondary level towards increasing entrepreneurial competencies, intentions, career choices, abilities and entrepreneurial self-efficacy (ESE) (Aamir et al, 2019). For this study, it is relevant to highlight that upper secondary and undergraduate education may play an essential role in students' personal growth, ESE and EI.…”
Section: Introductionmentioning
confidence: 96%
“…Community-based organizations offering small business training have also proliferated (Valerio et al , 2014). How gender is enacted within EET is, however, seldom considered (Aamir et al , 2019; Nabi et al , 2017). This includes understanding the construction of gender biases in course design, content, delivery and evaluation.…”
Section: Introductionmentioning
confidence: 99%